KAPABILITAS LEMBAGA OMBUDSMAN RI PERWAKILAN SUMATERA BARAT DALAM UPAYA PENCEGAHAN MALADMINISTRASI BIDANG PENDIDIKAN DI KOTA PADANG TAHUN 2023 - Darma, Revi Yulia; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is based on the number of public reports that have been submitted to the West Sumatra Representative Ombudsman regarding allegations of maladministration that occurred in the field of education, especially at the high school/equivalent level in Padang City. These problems need to be prevented by the Ombudsman to prevent repeated maladministration in the field of special education at the high school/equivalent level. This study aims to determine the capabilities of the West Sumatra Representative Ombudsman in an effort to prevent maladministration in the education sector in the city of Padang in 2023. The theory used is the Core Capability theory according to Leonard and Barton in Suherlan (2019). The methods used in this study are qualitative descriptive methods, data collection techniques through interviews and documentation, data analysis techniques are carried out through qualitative descriptive methods based on four stages, namely data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that the capability of the West Sumatra Representative Ombudsman in efforts to prevent maladministration in the education sector in the city of Padang in 2023 in the dimension of knowledge and skills has been maximized, but in the dimension of technical systems (technical systems) has not been maximized because the Ombudsman does not have a special SOP in preventing maladministration in the field of education, in the dimension of managerial systems (managerial system) has not been maximized because the Ombudsman Representative of West Sumatra has not reached all schools at the high school/equivalent level to carry out their duties in an effort to prevent maladministration in the field of education, and in the dimension of values and norms (values and norms) has not been maximized because the principle of balance has not been implemented properly because not all high schools/equivalents visited or interacted with the Ombudsman. This is due to the lack of human resources in the field of prevention at the West Sumatra Representative Ombudsman institution. Keywords : Capability, Maladministration, Ombudsman, Government, Education